The Conception of Literature in Three Short Stories by Roberto Bolaño - Camacho Guzmán, Gustavo (2016)
An analysis is carried out on how literature itself is conceived in the stories “Fotos,” “Dentista,” and “Encuentro con Enrique Lihn,” by Roberto Bolaño. These three texts offer a representation of the following components of the literary phenomenon: the writer (conceived as a miserable, poor, and suffering being), the reader (someone who suffers when reading), the text (a kind of executioner influencing the reader negatively), and the reading process (a condemning act).